Customer satisfaction : a case study of NTUC Fairprice supermarket. - Chin, Yue Fong. (2008)
The key constructs of customer satisfaction and attributes associated with supermarket shopping are discussed. A customer survey was carried out to determine factors that significantly affect overall customer satisfaction. The results indicate that product and service are relevant determinants of overall customer satisfaction. Implications are drawn and suggestions are highlighted.